Chronic exposure to 6:2 chlorinated polyfluorinated ether sulfonate acid (F-53B) induced hepatotoxic effects in adult zebrafish and disrupted the PPAR signaling pathway in their offspring. (June 2019) - Shi, Guohui; Cui, Qianqian; Wang, Jinxing; Guo, Hua; Pan, Yitao; Sheng, Nan; Guo, Yong; Dai, Jiayin
Abstract: As a Chinese-specific alternative to perfluorooctane sulfonate (PFOS), 6:2 chlorinated polyfluorinated ether sulfonate (commercial name: F-53B) has been used in the metal plating industry for over 40 years. This prevalence of use has resulted in its subsequent detection within the environment, wildlife, and humans. Despite this, however, its hepatotoxic effects on aquatic organisms remain unclear. Here, we characterized the impacts of long-term F-53B exposure on adult zebrafish liver and their offspring. Results showed that the concentration of F-53B was greater in the F0 liver than that in the gonads and blood. Furthermore, males had significantly higher liver F-53B levels than females. Hepatomegaly and obvious cytoplasmic vacuolation indicated that F-53B exposure induced liver injury. Compared to control, liver triglyceride levels decreased by 30% and 33.5% in the 5 and 50 μg/L-exposed males and 22% in 50 μg/L-exposed females. Liver transcriptome analysis of F0 adult fish found 2175 and 1267 differentially expressed genes (DEGs) in the 5 μg/L-exposed males and females, respectively. Enrichment analyses further demonstrated that the effects of F-53B on hepatic transcripts were sex-dependent. Gene Ontology showed that most DEGs were involved in multicellular organism development in male fish, whereas in female fish, most DEGs were related to metabolic processes and gene expression. qRT-PCR analysis indicated that the PPAR signaling pathway likely contributed to F-53B-induced disruption of lipid metabolism in F0 adult fish. In F1 larvae (5 days post fertilization), the transcription of pparα increased, like that in F0 adult fish, but most target genes showed the opposite expression trends as their parents. Taken together, our research demonstrated chronic F-53B exposure adversely impacts zebrafish liver, with disruption of PPAR signaling pathway dependent on sex and developmental stage. Graphical abstract: Image 1 Highlights: Accumulation of F-53B in zebrafish liver is sex-dependent. F-53B exposure induces hepatomegaly and decreases liver triglyceride levels. F-53B exposure results in differences between male and female hepatic transcripts. F-53B interferes with the PPAR signal pathway in adult fish and their offspring. Abstract : Long-term F-53B exposure induced hepatomegaly and disrupted lipid metabolism in F0 adult zebrafish and disturbed the transcriptional levels of genes involved in the PPAR signaling pathway in F1 larvae.